Dix contre un sur Espérance : une pièce sonore - Sarah Carton de Grammont; Anne Yvonne Guillou; Adeline Herrou; Sophie Houdart; Christine Jungen; Carolina Kobelinsky; Marion Langumier (Ateliers d'Anthropologie)
This sound piece distils a collective adventure that led seven anthropologists to examine nostalgia for lost field sites. Contrary to all expectations, it led from nostalgia to hope, by way of anticipation exercises. Through a choral reading of fiction fragments written by each of them, echoes between their texts were put to work. Without really having thought of it at the outset, they succeed in establishing a common language and jointly building a description of a shared profession, and of our world in crises.